The impact of screening for cardiovascular disease risk factors on population health and inequality. Evidence from the Stockport Screening Programme, United Kingdom (Italian Journal of Public Health, 2007)
Background: Population based screening for cardiovascular disease risk factors can potentially reduce coronary heart disease mortality and morbidity. There is little contemporary evidence that has examined the actual impact of such a programme on population health and on reducing inequality in health between affluent and deprived areas.Methods: 82,015 residents of Stockport Health Authority, UK age 35-60 took up an invitation to be screened for cardiovascular disease risk factors from 1989 -1999. We compared uptake of screening and coronary heart disease (CHD) mortality and hospital admissions (1997 – 2003) between screened and unscreened male and female populations from affluent and deprived areas.Results: Males and females in the unscreened population were more likely to die from CHD (IRR=3.60; p
Keywords: Cardiovascular risk; screening; health inequality; coronary heart disease